Evidence for Hydraulic Vulnerability Segmentation and Lack of Xylem Refilling under Tension . Issue 3 (9th September 2016) - Charrier, Guillaume; Torres-Ruiz, José M.; Badel, Eric; Burlett, Regis; Choat, Brendan; Cochard, Herve; Delmas, Chloe E. L.; Domec, Jean-Christophe; Jansen, Steven; King, Andrew; Lenoir, Nicolas; Martin-StPaul, Nicolas; et al.
Abstract : Direct, noninvasive observations of embolism formation and repair reveal a lack of refilling under negative pressure and a xylem hydraulic vulnerability segmentation in grapevine. Abstract: The vascular system of grapevine ( Vitis spp.) has been reported as being highly vulnerable, even though grapevine regularly experiences seasonal drought. Consequently, stomata would remain open below water potentials that would generate a high loss of stem hydraulic conductivity via xylem embolism. This situation would necessitate daily cycles of embolism repair to restore hydraulic function. However, a more parsimonious explanation is that some hydraulic techniques are prone to artifacts in species with long vessels, leading to the overestimation of vulnerability. The aim of this study was to provide an unbiased assessment of (1) the vulnerability to drought-induced embolism in perennial and annual organs and (2) the ability to refill embolized vessels in two Vitis species X-ray micro-computed tomography observations of intact plants indicated that both Vitis vinifera and Vitis riparia were relatively vulnerable, with the pressure inducing 50% loss of stem hydraulic conductivity = −1.7 and −1.3 MPa, respectively. In V. vinifera, both the stem and petiole had similar sigmoidal vulnerability curves but differed in pressure inducing 50% loss of hydraulic conductivity (−1.7 and −1 MPa for stem and petiole, respectively). Refilling was not observed as long as bulk xylem pressure remained negative (e.g. at the apical part of the plants; −0.11 ± 0.02 MPa) and change in percentage loss of conductivity was 0.02% ± 0.01%. However, positive xylem pressure was observed at the basal part of the plant (0.04 ± 0.01 MPa), leading to a recovery of conductance (change in percentage loss of conductivity = −0.24% ± 0.12%). Our findings provide evidence that grapevine is unable to repair embolized xylem vessels under negative pressure, but its hydraulic vulnerability segmentation provides significant protection of the perennial stem.